Morbidity and mortality in rheumatoid arthritis patients with prolonged and profound therapy-induced lymphopenia. - Isaacs, J; Greer, S; Sharma, S; Symmons, D; Smith, M; Johnston, J; Waldmann, H; Hale, G; Hazleman, B (2001)
OBJECTIVE: Therapies that deplete lymphocytes often improve symptoms in patients with otherwise refractory autoimmune disease but may result in long-term lymphopenia, the consequences of which are uncertain. To assess the impact of prolonged lymphopenia on morbidity and mortality, we studied patients who had previously received lymphocytotoxic monoclonal antibody (mAb) therapy for rheumatoid arthritis (RA). METHODS: Fifty-three patients who received the lymphocytotoxic mAb CAMPATH-1H between 1991 and 1994 in the United Kingdom were assessed for mortality and infectious and malignant morbidity, by interview and case-note review. In addition, patients were monitored via the National Health Service Central Registry, to verify notification of death. Peripheral blood lymphocyte subsets were analyzed by flow cytometry. A retrospective, matched-cohort study of mortality was also performed with 102 control subjects selected from the European League Against Rheumatism database, which comprises patients with rheumatic disorders who have received immunosuppressive drugs. RESULTS: There was profound and persistent peripheral blood lymphopenia in the mAb-treated patients, affecting predominantly the CD4+ subset. Median CD4+, CD8+, and CD19+ peripheral blood lymphocyte counts at 73-84 months after therapy were 185 cells/microl, 95 cells/microl, and 115 cells/microl, respectively. At a median followup of 71 months (range 14-90), 13 patients had died (24.5%), compared with 18% of the matched controls, providing a mortality rate ratio of 1.45 (95% confidence interval 0.65-3.13). During 283 patient-years of followup, there were 36 infections classified as major (12.7 per 100 patient-years). The causes of death and the spectrum of infections documented were similar to those expected in a hospital-based RA cohort. Patients who received more than 1 course of therapy had more severe lymphopenia than did patients who received a single course, but this did not have an impact on mortality or morbidity. CONCLUSION: Despite the occurrence of profound and long-lasting lymphopenia following treatment with antilymphocyte mAb therapy for RA, this therapy is not associated with a large excess of mortality nor with an unusual spectrum of infections, at least during a medium-term period of followup. These data are also relevant to patients receiving lymphocytotoxic mAb therapy for other indications, and to patients receiving other lymphodepleting therapies such as autologous stem cell transplantation.